(Ukrajina, Belorusija, Moldavija in Estonija) - Uhlik, Mladen (Monitor ISH, 2004)
Examples of language policy in the former Soviet republics. The study portrays some aspects of the sociolinguistic situation in the states of the former Soviet Union. Since this is their first period of sovereignty in modern history, one of their first tasks has been to organise their language policy, that is, to promote their own national languages and define the policy on minority languages. A special problem is posed by Russian, which had been the lingua franca for years. Four examples of different language policies treated in the paper reveal that the issue goes beyond purely linguistic debates. As a key instrument of constructing the national identity, language has a symbolic function. It is also important in establishing the attitude to the Other.
Keywords: jezikovna politika; manjšine; narodna identiteta; nacionalni jezik; sociolinguistics; sociolingvistika; Ukraine; Ukrajina; Belorusija; Moldavija; Estonian Soviet Socialist Republic; Estonija